+9y=813x+y=+4y=358x+3y=+2y=527x+4y=+6y=549x+2y=+y=72x+5y=+2y=213x+5y=+7y=525x+2y=+5y=657x+7y=+4y=56x+4y=+7y=415x+8y=+5y=543x+4y=+8y=154x+y=+6y=249x+5y=+2y=624x+3y=+4y=467x+4y=+7y=1354x+y=+8y=51x+6y=+3y=994x+7y=+2y=383x+6y=+5y=457x+9y=+2y=287x+8y=+6y=143x+3y=+4y=672x+8y=+4y=527x+6y=+y=94x+6y=+6y=486x+3y=+2y=167x+y=+9y=778x+6y=+8y=687x+6y=+2y=227x+2y=+3y=83x+5y=-7y=5x+2y=-8y=14x+y=+7y=3x+y=+y=107x-y=+10y=27x+y=-y=0x+y=-y=1211y-x=-+6y=272x+3y=-2y=4x+2y=1241.(2x+y)-5y=22x-5y=-3y=33x+2y=+2y=21y-6x=-8y=03x-2y=+y=105x-7y=-2y=1x-y=3x+3y=-53x-4y=-2y-3x=2x-2y=65x+3y=22x-y=39x-3y=122x+y=62x+3y=73x+2y=33x+2y=18x+y=-5y=1x+y=+8y=4425x+6y=4803x-2y=57x-4y=113x-5y=22x-y=34x-3y=182x-y=8x-2y=5x+3y=-53x+y=72x+3y=73x-2y=72x-3y=+17y=6317x+23y=-y=2x+1=2(y-1)-5y=03x+2y=+2=42(y-3)=(y-2)=x-12(x-1)=5y-+2y+2=07x-4y=-41x-3y+20=03x+7y-100=+y=13x-2y=-93x-4y+11=03y-4x+53=04y=3x+45y=4x+37x-3y+1=04x-5y=-173x-y-3=04x+3y=-y=32y+3(x-y)=-4y=23(x-4)=4(y+2)3x+2y=102(x+1)-y=112(2x+y)-5=7y6x+6y=486x+3y=42(2x+y)-5y=22x-5y=+y=(x-4)=4(y+2)-3y=-53x+2y=-2(x+2y)=311x+4(x+2y)=-2y=+2y=203x+4y=-=-9y=12-4x+3y=-53x+5y=66x+15y=-y-3=04x+3y=+y=+=+4y=+5y=198x-3y=-1=3y+-2y=71-3x=+=+=88
二元一次方程组计算题100题 来自淘豆网m.daumloan.com转载请标明出处.